2018
DOI: 10.1080/10245332.2018.1436395
|View full text |Cite
|
Sign up to set email alerts
|

Mometasone furoate inhibits growth of acute leukemia cells in childhood by regulating PI3K signaling pathway

Abstract: This study reveals that MF can inhibit proliferation and invasion/migration and induce apoptosis in Childhood ALL cells, which may be regulated by Phosphatidylinositol 3-kinase signaling pathway. These results suggest MF may be a potential new drug target for clinical ALL treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Since glucocorticoids could promote cell apoptosis via binging with glucocorticoid receptors in lymphoid cells, most extensive application of glucocorticoids in cancer is to treat lymphoid malignancies [23,34]. Consistent with that, it was reported MF could inhibit the growth of acute leukemia cells through promoting cell apoptosis [10]. While there was still no exploration of the pharmacological effect of MF on solid tumor.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Since glucocorticoids could promote cell apoptosis via binging with glucocorticoid receptors in lymphoid cells, most extensive application of glucocorticoids in cancer is to treat lymphoid malignancies [23,34]. Consistent with that, it was reported MF could inhibit the growth of acute leukemia cells through promoting cell apoptosis [10]. While there was still no exploration of the pharmacological effect of MF on solid tumor.…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies regarding MF mostly focused on its treatment for in ammation. In a recent study, MF inhibited the growth and induced the apoptosis of acute leukemia cells by regulating PI3K signaling pathway [10]. For the above-mentioned reasons, MF could be identi ed as a promising anti-cancer drug for HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…In the pathogenesis of ALL, several members of the PI3K/AKT pathway, including AKT1, AKT2, PTEN, and BCL-2, have been implicated. [8][9][10] This study focuses on the impact of SNPs in miRNAs that are known to target these genes. Genetic variants occurring in miRNA sequences can alter binding ability or processing of mature miRNAs, which can subsequently affect the expression of their target coding genes at an epigenetic level.…”
Section: Discussionmentioning
confidence: 99%
“…7 For example, Wang et al have shown that the expression of p-AKT decreased in ALL cell lines treated with mometasone furoate. 8 Paganin et al found that PTEN genomic aberrations and PTEN inactivation contributed to adverse therapy response in T-ALL patients. 9 Khaw et al have reported that venetoclax, a selective inhibitor of BCL-2, exhibited effective antileukemic activity in the majority of ALL xenografts.…”
Section: Introductionmentioning
confidence: 99%
“…Hulkko et al (56,57) reports that DAP3 interacted with GR mainly via the N-terminal region of DAP3, modulating the cytoplasmic GR-hsp90 complex, finally induced apoptosis. Wang et al (58) found that mometasone furoate could inhibit proliferation and migration of acute leukemia cells via regulating PI3K signaling pathway.…”
Section: Glucocorticoids As Therapeutic Agentsmentioning
confidence: 99%